2018
DOI: 10.1016/j.jpain.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Medication Use Among Community-Based U.S. Adults With Chronic Low Back Pain: A Cross-Sectional Population Based Study

Abstract: Because prescription opioid use is an issue of national concern, we examined pain-related prescription medication use in community-dwelling U.S. adults with cLBP. Opioids were the most common prescription pain medication, typically used long-term, in combination with other central nervous system-active agents, and disproportionately among individuals with less than a college education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 56 publications
(58 reference statements)
1
49
0
4
Order By: Relevance
“…The baseline characteristics of the study population were analysed by drug group. Categorical variables were presented as number and percentage and continuous variables as mean and standard deviation (SD), and compared using Chi test with 2 degrees of freedom and Kruskal–Wallis test. Subjects were censored at death date, last dispensing date or 31 December 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics of the study population were analysed by drug group. Categorical variables were presented as number and percentage and continuous variables as mean and standard deviation (SD), and compared using Chi test with 2 degrees of freedom and Kruskal–Wallis test. Subjects were censored at death date, last dispensing date or 31 December 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Pregabalin and gabapentin, originally presented as anticonvulsants, are now increasingly prescribed for a range of clinical conditions, in particular for chronic pain . These drugs selectively bind to the α2‐δ subunit of voltage‐gated calcium channels in central nervous system neuronal tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Although this angle became less vertical, the authors do not necessarily feel that this was a negative result. It has been found that sitting in a more active, erect position requires more muscle activity than sitting in other, more relaxed positions [12,13]. Therefore this increased trunk thigh angle most likely reflects a more relaxed sitting position after becoming accustomed to the device and using it for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen percent of these had used opioids, 10% took non-steroidal anti-inflammatory drugs (NSAIDs), 8.5% took muscle relaxants, and 7% used gabapentinoids. Antidepressants and hypnotics were used by 18% and 5%, respectively [12]. This survey showed that analgesic polypharmacy is common, though guidelines on the use of medications for LBP highlight the small benefit from these therapies.…”
Section: Overview Of Pharmacological Options For Low Back Painmentioning
confidence: 98%
“…Opioids are the most commonly used prescription medication for chronic LBP, with one in five Americans using them to treat pain and a majority using them chronically [12]. Similar to all other analgesic medications, there is limited evidence in the form • Epidural S(+) ketamine enhanced analgesic effects of steroids and local anesthetics and reduced disability in patients with LBP and radicular pain • Subanesthetic intravenous ketamine (mean dose 0.9 mg kg −1 ) in severe refractory pain states reduced pain for over 3 weeks • Epidural ketamine may be associated with neurotoxicity of controlled trials supporting opioid use beyond 4 months, though long-term use is associated with an increased risk of abuse and overdose.…”
Section: Opioidsmentioning
confidence: 99%